2022
DOI: 10.1021/acsomega.2c05891
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 3-Phenylquinoline Derivative PQ1 as an Antagonist of p53 Transcriptional Activity

Abstract: Transcription factor p53 regulates cellular responses to environmental perturbations via the transcriptional activation of downstream target genes. Inappropriate p53 activation can trigger abnormal cellular responses, therefore leading to acute or chronic tissue damage, human developmental syndromes, and neurodegenerative diseases. Antagonists of p53 transcriptional activity provide prospective therapeutic applications and molecular probes. In this article, we identified five 3-phenylquinoline derivatives as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…Our results suggest that CENPN might regulate p53 expression through MDM2-mediated degradation. To further examine the relationship between CENPN and p53 transcriptional activity, we treated PAAD cells downregulated for CENPN with PFTα, a p53 inhibitor that inhibits its transcriptional activity by blocking its binding to DNA [43,44]. The results showed that the effect of si-CENPN on promoting apoptosis of PAAD cells was weakened after treatment with PFTα, suggesting that CENPN-mediated apoptosis in PAAD cells may be related to p53 transcriptional activity.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that CENPN might regulate p53 expression through MDM2-mediated degradation. To further examine the relationship between CENPN and p53 transcriptional activity, we treated PAAD cells downregulated for CENPN with PFTα, a p53 inhibitor that inhibits its transcriptional activity by blocking its binding to DNA [43,44]. The results showed that the effect of si-CENPN on promoting apoptosis of PAAD cells was weakened after treatment with PFTα, suggesting that CENPN-mediated apoptosis in PAAD cells may be related to p53 transcriptional activity.…”
Section: Discussionmentioning
confidence: 99%